Improving the Heat Transfer using Fe3O4 Nanoparticles Suspended in Water Flow through Circular Tube - Hussain, hamed J. (Journal of Petroleum Research and Studies, 2022)
The new class of pressure drop and heat transfer enhancement through pipes and heat exchangers is defined a nano-fluid. The applications of this process are the cooling of oil inside heat exchanger and the flow of oil into the pipe line. In this work, the prediction of heat transfers and friction factor in a heated tube is studied. ANSYS software of CFD simulation through the geometrical problem undertaken was utilized. The Fe3O4 nanoparticles suspended in pure water has been adopted to flow through the test rig under ranges of nanoparticles mass concentrations and Reynolds number 1% to 4% and 4000 to 10000 respectively. The numerical results show that the friction factor and heat transfer enhancement increase as increase of nanoparticles mass concentrations 23% and 4% respectively. Additionally, the heat transfer is increased and the friction factor is decreased as increase of Reynolds number. It was concluded that Nusselt number increases due to add the solid nanoparticles to the water but slightly increases of pumping power. This obtained results are validated with the available data in the literature.